Squatters on railway land: legal issues and recommendations - Abdul Jalil, Najah Inani (Global Academic Excellence, 2018)
The advancement of railway transportation in Malaysia is one of the focus areas in the national development plan. The railway authorities are allocated with reserved land for purposes of railway tracks development. The reserved land is often occupied by unauthorised persons who are termed as squatters pursuant to the National Land Code (Act 56 of 1965). The objective of this article is to identify the challenges in enforcing the law and procedures relating to the eviction of squatters from the railway land. The methodology adopted is literature review to establish the issues relating to the management of squatters generally and squatters living on railway land specifically. The discussion will also focus on the powers of the State Authority, local authority and railway authority in dealing with the squatters on railway reserved land and propose a mechanism to improve the present system to overcome the weaknesses in enforcing of the law relating to eviction of squatters on railway land.